2011
DOI: 10.1002/gps.2796
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based trajectories of depressive symptoms and the predictors in the older population

Abstract: Older females may experience more emotional fluctuation than male elderly, thus changes in psychosocial health for female elderly need to be considered by health professionals and families. Social support and social participation are protective against depressive symptoms for the higher-level trajectory groups, and older men, in particular, are more sensitive to these two social-health-related variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
45
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 37 publications
(56 reference statements)
16
45
4
1
Order By: Relevance
“…About two thirds of the men and women belonged to a never-depressed group, and only a minority reached high depressive scores. These findings are in line with previous studies on depressive trajectories in older people (Andreescu et al, 2008;Kuchibhatla et al, 2011;Kuo et al, 2011;Liang et al, 2011;Byers et al, 2012;Hsu, 2012). Nevertheless, 7% of the men and 11% of the women had a trajectory that was constantly above the French threshold for the CES-D and could therefore be considered as chronically clinically depressed, which is problematic given the personal and public health burden of later-life depression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…About two thirds of the men and women belonged to a never-depressed group, and only a minority reached high depressive scores. These findings are in line with previous studies on depressive trajectories in older people (Andreescu et al, 2008;Kuchibhatla et al, 2011;Kuo et al, 2011;Liang et al, 2011;Byers et al, 2012;Hsu, 2012). Nevertheless, 7% of the men and 11% of the women had a trajectory that was constantly above the French threshold for the CES-D and could therefore be considered as chronically clinically depressed, which is problematic given the personal and public health burden of later-life depression.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have investigated the course of depressed mood among community-dwelling older adults by examining individual trajectories of depressive symptoms, with consistent results (Andreescu et al, 2008;Kuchibhatla et al, 2011;Kuo et al, 2011;Liang et al, 2011;Hsu, 2012). All showed that a majority (between 75% and 90%) of older people experienced no or only mild depressive symptoms and that a minority exhibited an increasing, decreasing or persistently severe trajectory.…”
Section: Introductionmentioning
confidence: 94%
“…They found equal numbers (6%) of men and women in the “persistent depression” class, but fewer women (58% vs. 72%) in the “no depression” class. Hsu et al (2012) examined 18-year trajectories of depressive symptoms in older adults and again found similar patterns among males and females, but more females than males in the trajectory classes characterized by higher symptoms, particularly the increasing and declining classes. Finally, Montagnier et al (2014) examined 20-year trajectories in older adults and found that while both groups contained a “no depression” class and an “increasing depression” class, the most symptomatic class in women displayed stable high symptoms over time, while the most symptomatic class in men exhibited a fluctuating pattern in which symptoms decreased slightly and then began to rise in a linear fashion with age.…”
Section: Resultsmentioning
confidence: 82%
“…However, there is another possibility that has not been used in studies of IFN-MDD. In this third approach, distinct trajectories of depressive symptoms over time can be classified using data-driven techniques such as group-based growth mixture models (5053). These depression trajectories are defined as changes in the course of an individual’s depressive symptoms over time, with the advantage of making it possible to detect changes at both the group level and the individual level.…”
mentioning
confidence: 99%